PENGARUH KEHARMONISAN KELUARGA DAN LINGKUNGAN SOSIAL SEKOLAH TERHADAP VANDALISME REMAJA SMP NEGERI 14 PONTIANAK - Muliyani, Muliyani; Bahari, Yohanes; Rustiyarso, Rustiyarso (Jurnal Kajian Pembelajaran dan Keilmuan, 2021)
AbstractÂ This study aims to determine the interaction of family and social environment on the vandalism behavior of eighth grade students of SMP Negeri 14 Pontianak. This research method is quantitative with a research sample of 110 VIII students using purposive sampling. Data was taken using a questionnaire. The results showed that vandalism was low at 60.8%, family harmony was 44.7% and the school environment was categorized as very high at 34.4%. The results of the test show Fcount (31,328) > Ftable (3.08) and a significance of 0.00 < 0.05, meaning that family harmony and social environment have a significant effect on vandalism behavior. tcount of the decent family harmony variable -4.486 > ttable 1.982 with a significance of 0.00 <0.05, which means that there is a significant negative effect. tcount of the appropriate school social environment variable -2.547 > ttable 1.982 with a significance of 0.01 <0.05, which means that there is a significant negative effect. Regression equation Y'= 68.074+ (- 0.418) + (-0.313) + e. The determinant value of Adjusted R2 = 0.358, which means that the influence of family interaction and social environment on vandalism behavior is low, namely 35.8%.Â Keywords: Harmonious Family, School Social Environment, Vandalism.